Analysis of the Nature of Sign from the Perspective of Saussure and Farabi - Neda Rāhbār; Mahdi Khabazi Kenari (آموزه‌‌های فلسفه اسلامي, 2020)
Semiotics is an important part of Saussure’s serious studies in the field of linguistics. According to Saussure, the nature of the sign is divided into signifier and signified. In the common sense, the signifier is something outside the mind and the signified is something inside the mind. Saussure, however, following Kant, challenges the customary view and considers the origin of the production of them enclosing in mind. In the tradition of Islamic philosophy, Farabi is the first linguistic philosopher to pay attention to the contemporaneous structure of language, regardless of its historical aspect. Using the concept of word and reason, while reading the relations between them conventionally, he offers a subjectivist reading of the analysis of the nature of signs. The present article has two purposes: 1st, Saussure and Farabi’s views on the nature of the sign will be examined. 2nd , Farabi’s view of the letter and reasonable and how they relate to Saussure’s signified will be analyzed.